1980
DOI: 10.1007/bf01402765
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory study of metal-resistant sliding-gate tiles

Abstract: Sliding gates are becoming more and more widely used in steel casting in Soviet steelworks. Experience of the use of these gates is constantly being analyzed. On the basis of these analyses, the specifications for the refractory materials are refined and the operational conditions during casting improved.The main factor determining the reliable operation of the gates is their metal resistance, i.e., the ability of the material of the refractory tiles to withstand the aggressive action of liquid steel. From 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1980
1980
1985
1985

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…Thus, this study of the wear on the tiles of a sliding-gate steel-casting s y s t e m has confirmed the results of previous laboratory studies [5,9] and has made it possible to determine the limiting structural changes in the r e f r a c t o r i e s . At the contact between the r e f r a c t o r y and the current of liquid steel, these changes may be c h a r a c t e r i z e d by the fact that the m a s s fraction of the main component of the p e r i c l a s e articles is lowered to 25-30% and that of the corundum to 60-65%.…”
Section: <_ 250~supporting
confidence: 80%
See 2 more Smart Citations
“…Thus, this study of the wear on the tiles of a sliding-gate steel-casting s y s t e m has confirmed the results of previous laboratory studies [5,9] and has made it possible to determine the limiting structural changes in the r e f r a c t o r i e s . At the contact between the r e f r a c t o r y and the current of liquid steel, these changes may be c h a r a c t e r i z e d by the fact that the m a s s fraction of the main component of the p e r i c l a s e articles is lowered to 25-30% and that of the corundum to 60-65%.…”
Section: <_ 250~supporting
confidence: 80%
“…The network of c r a c k s which forms is clear in the fragment (a) of specimen 1 (Fig. 2).. With casting on MNLZ, the features of the thermal load in the supporting region lead p r i m a r i l y to the extension of the c r a c k s which have formed in origin to those described in [5] (Fig. 2, fragment b of specimen 2).…”
Section: <_ 250~mentioning
confidence: 86%
See 1 more Smart Citation
“…The metal resistance of specimens with the coatings determined in molten Armco iron at 1600~ using the known method [9] increases by 18-25% in comparison with the original refractories.…”
Section: 6mentioning
confidence: 99%
“…This article deals with the action of rimmed steels on periclase and corundum refractories. * * The investigation procedure was described in [1]. • 40.…”
mentioning
confidence: 99%